2013
DOI: 10.1159/000350777
|View full text |Cite
|
Sign up to set email alerts
|

Patient's Anastrozole Compliance to Therapy (PACT) Program: Baseline Data and Patient Characteristics from a Population-Based, Randomized Study Evaluating Compliance to Aromatase Inhibitor Therapy in Postmenopausal Women with Hormone-Sensitive Early Breast Cancer

Abstract: Background: The Patient's Anastrozole Compliance to Therapy (PACT) program is a large randomized study designed to assess whether the provision of educational materials (EM) could improve compliance with aromatase inhibitor therapy in postmenopausal women with early, hormone receptor-positive breast cancer. Patients and Methods: The PACT study presented a large, homogeneous dataset. The baseline analysis included patient demographics and initial treatments and patient perceptions about treatment and quality of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…The EvaluateTM study is one of three prospective studies with a large number of patients which have considered the issue of compliance in aromatase inhibitor therapy. The PACT study (Patientʼs Anastrozole Compliance to Therapy) was a prospective randomized study which also included around 5000 patients [24]. In the PACT study, patients were randomized into one of two groups: one group where patients regularly received information about the disease and the anti-hormone treatment during the first year of treatment and one group which did not receive this regular information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EvaluateTM study is one of three prospective studies with a large number of patients which have considered the issue of compliance in aromatase inhibitor therapy. The PACT study (Patientʼs Anastrozole Compliance to Therapy) was a prospective randomized study which also included around 5000 patients [24]. In the PACT study, patients were randomized into one of two groups: one group where patients regularly received information about the disease and the anti-hormone treatment during the first year of treatment and one group which did not receive this regular information.…”
Section: Discussionmentioning
confidence: 99%
“…In the PACT study, patients were randomized into one of two groups: one group where patients regularly received information about the disease and the anti-hormone treatment during the first year of treatment and one group which did not receive this regular information. The study population receiving adjuvant treatment was very similar to that of the Evalua-teTM study [24]. Randomization in the PACT study was analyzed with regard to compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that educational materials and reminders did not increase adherence to ET [29][30][31]. Two randomized trials that compared educational materials about ET with standard care showed no difference in adherence after 1 year [29,32]. Another intervention trial with a small sample compared standard care versus mailings (5 letters year 1 and 3 letters year 2) versus telephone calls (5 calls year 1; 3 calls year 2) to improve adherence to aromatase inhibitors [31].…”
Section: Mini Reviewmentioning
confidence: 99%
“…Heruntergeladen [24]. In dieser Studie wurde eine Randomisierung durchgeführt, welche die Patientinnen in eine Gruppe einteilte, die regelmäßig im 1.…”
unclassified
“…Jahr Informationen über die Erkrankung und die Antihormontherapie erhalten hatte, und eine Gruppe, die diese Informationen nicht regelmäßig erhalten hatte. Diese Studienpopulation in der adjuvanten Situation war der der EvaluateTM-Studie sehr ähnlich [24]. Die Randomisierung wurde in der PACT-Studie im Hinblick auf die Compliance untersucht.…”
unclassified